Bio‐Inspired Photonic Materials: Prototypes and Structural Effect Designs for Applications in Solar Energy Manipulation. (30th November 2017) - Zhou, Han; Xu, Jun; Liu, Xianghui; Zhang, Haiwen; Wang, Dantong; Chen, Zhihan; Zhang, Di; Fan, Tongxiang
Abstract: Natural creatures have evolved elaborate photonic nanostructures on multiple scales and dimensions in a hierarchical, organized way to realize controllable absorption, reflection, or transmitting the desired wavelength of the solar spectrum. A bio‐inspired strategy is a powerful and promising way for solar energy manipulation. This feature article presents the state‐of‐the‐art progress on bio‐inspired photonic materials on this particular application. The article first briefly recalls the physical origins of natural photonic effects and catalogues the typical natural photonic prototypes including light harvesting, broadband reflection, selective reflection, and UV/IR response. Next, typical applications are categorized into two primary areas: solar energy utilization and reflection. Recent advances including solar‐to‐electricity, solar‐to‐fuels, solar‐thermal (e.g., photothermal converters, infrared detectors, thermoelectric materials, smart windows, and solar steam generation) are highlighted in the first part. Meanwhile, solar energy reflection involving infrared stealth, radiative cooling, and micromirrors are also addressed. In particular, this article focuses on bioinspired design principles, structural effects on functions, and future trends. Finally, the main challenges and prospects for the next generation of bioinspired photonic materials are discussed, including new design concepts, emerging ideas, and possible strategies. Abstract : Bio‐inspired photonic design is a powerful and promising way for solar energy manipulation. This Feature Article presents the state‐of‐the‐art progress of bio‐inspired photonic materials. Typical natural photonic prototypes including light harvesting, broadband reflection, selective reflection, and UV/Infrared response are summarized. Solar energy manipulation applications including solar‐to‐electricity, solar‐to‐fuels, solar–thermal (photothermal converters, infrared detectors, thermoelectric materials, etc.), and solar energy reflection are highlighted.